2016
DOI: 10.1093/mnras/stw2751
|View full text |Cite
|
Sign up to set email alerts
|

The deep OB star population in Carina from the VST Photometric Hα Survey (VPHAS+)

Abstract: Massive OB stars are critical to the ecology of galaxies, and yet our knowledge of OB stars in the Milky Way, fainter than V ∼ 12, remains patchy. Data from the VST Photometric Hα Survey (VPHAS+) permit the construction of the first deep catalogues of blue excess-selected OB stars, without neglecting the stellar field. A total of 14900 candidates with 2MASS cross-matches are blue-selected from a 42 squaredegree region in the Galactic Plane, capturing the Carina Arm over the Galactic longitude range 282 • 293 •… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 77 publications
(108 reference statements)
0
42
0
Order By: Relevance
“…The blue curve represents the stellar locus from the PARSEC isochrones (Marigo et al 2017) and the red line shows the reddening curve of the B3V stars from Drew et al (2014). Pink dots are O-B2 candidates from Mohr-Smith et al (2017. Gaia DR2 provides high precision photometric measurements of over 1.4 billion sources in G, G BP and G RP bands.…”
Section: Vphas+ and Gaiamentioning
confidence: 99%
See 1 more Smart Citation
“…The blue curve represents the stellar locus from the PARSEC isochrones (Marigo et al 2017) and the red line shows the reddening curve of the B3V stars from Drew et al (2014). Pink dots are O-B2 candidates from Mohr-Smith et al (2017. Gaia DR2 provides high precision photometric measurements of over 1.4 billion sources in G, G BP and G RP bands.…”
Section: Vphas+ and Gaiamentioning
confidence: 99%
“…Similarly to Mohr-Smith et al (2015) and Mohr-Smith et al (2017), we first select OB star candidates with the (u´g, g´r) colourcolour diagram. In the diagram, the reddened OB stars of spectral types earlier than B3 are easily identifiable as they are located above and away from the main stellar locus.…”
Section: Ob Star Candidates From Vphas+ and Gaiamentioning
confidence: 99%
“…In earlier work (Mohr-Smith et al 2015, 2017, hereafter MS-I and MS-II), we presented blue selections of OB stars from the VST Photometric Hα Survey of the Southern Galactic Plane and Bulge (VPHAS+, Drew et al 2014) across the Carina region, and showed that their conversion to spectroscopically-confirmed OB stars is very high. The MS-II list of 5915 O-B2 candidates is accompanied by highquality measures of extinction, along with estimates of ef-fective temperatures that are good enough to broadly classify as early-O, later-O and early-B stars.…”
Section: Introductionmentioning
confidence: 99%
“…According to the tests with Hipparcos Input Catalogue (HIC, Turon et al 1993) and Tycho-2 Spectral Types (TST) catalog (Wright et al 2003), 14,732 (94 %) of them are of O-to A0-type (Gontcharov 2012). Mohr-Smith et al (2017) selected 14,900 early-type stars with 5,915 high confidence O-B2 stars with T eff from SED fitting, but these stars are limited in 42 deg 2 in the Carina Arm region with high interstellar extinction. Galactic O-Star Spectroscopic Survey (GOSSS;Maz Apellniz et al 2011;Sota et al 2014;Maz Apellniz et al 2016) is a project dedicated to O-type stars.…”
Section: Introductionmentioning
confidence: 99%